Green Competence Building, Green Employee Involvement and Green Work-Life Balance to Improve Environmental Performance through Green Organizational Culture - PRASETYO, Deni Widyo; KUSMANINGTYAS, Amiartuti; MUJANAH, Siti (Journal of Environmental Management and Tourism; Vol 15 No 1 (2024): JEMT, Volume XV, Issue 1(73), Spring 2024, 2024)
This research is motivated by environmental performance. The aim of this study is to determine the influence of the relationship between green competence building, green employee involvement, and green work-life balance on environmental performance, mediated by the green organizational culture of the Head of Study Program at PGRI Higher Education Institutions in East Java. The grand theory of this research is the AMO theory (Ability, Motivation, Opportunity). The sampling technique uses a saturated or census sample. The sample in this study consists of 185 respondents, the Head of Study Program at PGRI Higher Education Institutions in East Java, through a self-administered survey. The research instrument uses a questionnaire and is analyzed using SEM analysis, employing the Warp PLS Version 7.0 analysis tool to analyze the outer model, inner model, and hypothesis testing using p-value. The results show a significant direct influence of green competence building and green employee involvement on green organizational culture. Subsequently, green organizational culture significantly influences environmental performance. The relationship with green work-life balance does not significantly affect green organizational culture. This research indicates that there is an intervening variable effect, namely green organizational culture, on the relationship between green competence building, green employee involvement, and environmental performance. However, green organizational culture cannot act as an intervening variable in the relationship between green work-life balance and environmental performance. This study demonstrates that the practices of green competence building, green employee involvement, and green organizational culture play a crucial role in the implementation of environmental policies to promote environmental performance at PGRI Higher Education Institutions in East Java.